2018
DOI: 10.1371/journal.pone.0201222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of costimulatory molecules in dogs with B cell high grade lymphoma

Abstract: B cell high grade lymphoma is the most common hematopoietic malignancy in dogs. Although the immune checkpoint molecules, programmed death-1 (PD-1) and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), and immune checkpoint inhibitors have been evaluated for the treatment of various human lymphoid malignancies, the expression of those molecules and their relationship with prognosis remain unknown in canine lymphoma. The objective of this study was to evaluate the expression of costimulatory molecules on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…costimulatory molecule in circulating cells during neoplastic disease and in a healthy subject. [77][78][79] Our results, although preliminary, highlight the presence of this molecule within canine melanoma and open the path for new investigations on the role of CTLA-4-associated pathways in canine oncology. IDO can be expressed by different cell types, in particular MDSCs, DCs, macrophages, and tumor cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…costimulatory molecule in circulating cells during neoplastic disease and in a healthy subject. [77][78][79] Our results, although preliminary, highlight the presence of this molecule within canine melanoma and open the path for new investigations on the role of CTLA-4-associated pathways in canine oncology. IDO can be expressed by different cell types, in particular MDSCs, DCs, macrophages, and tumor cells.…”
Section: Discussionmentioning
confidence: 58%
“…To the best of our knowledge, this is the first study focusing on CTLA-4 within canine melanoma microenvironment; previous studies aimed at characterizing the expression of this costimulatory molecule in circulating cells during neoplastic disease and in a healthy subject. 77 79 Our results, although preliminary, highlight the presence of this molecule within canine melanoma and open the path for new investigations on the role of CTLA-4-associated pathways in canine oncology.…”
Section: Discussionmentioning
confidence: 61%
“…There are multiple reports of the expression of immune checkpoints in InvUC and other cancers in dogs (148)(149)(150)(151)(152)(153)(154)(155)(156)(157). In addition to the well-known checkpoints PD-1, PD-L1, CTLA-4, other checkpoints have been identified in canine InvUC (59, 157).…”
Section: Growing Role For the Dog Model To Drive Advances In Emergingmentioning
confidence: 99%
“…In canine oncology, the tumor microenvironment and immune system are less investigated. However, it has been recently shown that PD-1 and CTLA-4 are significantly overexpressed by peripheral blood T lymphocytes in cancer-bearing dogs compared with in healthy controls [126,127] and that PD-1 blockade enhances T-cell activation [127]. Alongside that, PD-L1 was shown to be expressed in many canine cancers, including oral melanoma [35,128,129].…”
Section: Innovative Therapies In Human and Canine Melanomasmentioning
confidence: 99%